Wartości moralne i estetyczne na łamach paryskiej "Kultury" = Moral and esthetic values in the Parisian "Kultura" - Górka, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"Kultura", a journal published from 1947 by Instytut Literacki in Paris, was founded by Redactor Jerzy Giedroyc. On its pages were published mainly political articles, but also texts the main known Polish writers, eg. Witold Gombrowicz, Czesław Miłosz, Gustaw Herling-Grudziński and the others. Writers, who are published in "Kultura" in 1953, prepared their texts about different topics.
Keywords: "Kultura" (paryska) - czasopismo; wartości moralne; wartości estetyczne; Parisian "Kultura"; moral values; esthetic values